A Narrative Review of Known Plants which Have Potential Benefits as Natural Galactagogues in Indonesia - Winata, Grace Marlina; Hardinsyah Hardinsyah; Sri Anna Marliyati; Rimbawan Rimbawan; Dimas Andrianto (Universitas Airlangga, 2024)
Human milk is the gold standard for infant nutrition during the first six months of life. According to Indonesia Demographic and Health Survey in 2017, about 45% of mothers in Indonesia provided pre-lacteal feeding within three days postpartum. Low or no milk production and perceived insufficient milk for the infants need were common reasons for pre-lacteal feeding. Galactagogues are believed to help augment human milk production. Therefore, galactagogue consumption is highly recommended, especially natural galactagogue, to help overcome low milk production problem. Most natural galactagogues are used as a local tradition only. Scientific studies regarding the phytochemical compounds and the mechanisms involved are still very limited. This narrative review aimed to describe selected research articles reporting the potency of torbangun, katuk, kelor, and papaya leaves as known plants acting as natural galactagogues in Indonesia. A total of 22 original research articles from Indonesia written in Indonesian or English over a 20 years period were included in this review. Studies were selected if selected natural galactagogues were evaluated at least for the proposed mechanism of action and effects. The data have shown strong evidence about the positive effect of torbangun, katuk, kelor, and papaya leaves as natural galactagogues on increasing human milk production. The five leaves contain different phytoestrogens that have an estrogen effect to stimulate prolactin production and increase milk production.